Decoupled control of attraction force and propulsion force in linear induction motor drive - Rathore A.K.; Mahendra S.N. (My University, 2025)
As a special and distinct feature, the linear induction motor generates attractive force between the primary and secondary members in addition to the propulsive force, which brake the motion during accelerating as well as imposes the control problem owing to the coupled flux and motion dynamics with the advantage of reducing the possibility of derailment. In the present paper, the authors have made an effort to decouple the flux and motion dynamics for independent control of attraction and propulsion forces. This control strategy allows high performance to be achieved from LIM. The present paper deals with the performance investigation of LIM driven by three PI controllers using commercially available software package Matlab/Simulink. © 2003 IEEE.